Handbook of Life Course Health Development 2017
DOI: 10.1007/978-3-319-47143-3_16
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease: A Life Course Health Development Perspective

Abstract: Chronic kidney disease (CKD) reflects life events that range from maternal-fetal influences to geriatric exposures. The global direct and indirect costs of CKD are high and include maternal-neonatal hospitalization and treatment, acute kidney injury, dialysis and transplant, missed work, and medications, to name a few. The impact of poor diet, adverse childhood experiences, medication use, and failure to follow consistent public health standards are increasingly appreciated as key influences in the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 185 publications
(238 reference statements)
0
7
0
2
Order By: Relevance
“…Only two animal studies and one epidemiological study indirectly addressed this research question [ 33 , 36 , 38 ]. Specifically, we found no studies addressing psychosocial determinants of kidney health in early childhood, an area that remains a critical research need [ 39 ]. We included studies that reported associations between different psychosocial stressors (low socio-economic status, racial discrimination, migration, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two animal studies and one epidemiological study indirectly addressed this research question [ 33 , 36 , 38 ]. Specifically, we found no studies addressing psychosocial determinants of kidney health in early childhood, an area that remains a critical research need [ 39 ]. We included studies that reported associations between different psychosocial stressors (low socio-economic status, racial discrimination, migration, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is essential to acknowledge that exposure to chemical substances may have a synergistic effect in perinatal outcomes when pregnant women are co-exposed to psychosocial stressors and other environmental toxicants, both individually and at a community level [ 44 , 45 , 46 ]. As is the case for preterm birth, wherein concomitant exposure to adverse life events (e.g., poverty, racism, inequitable access to healthcare) as well as an individual’s exposure to environmental toxicants (e.g., air pollution, metals, some pesticides, or phthalates), may also damage developing kidneys, reducing nephron endowment over the life course [ 38 , 47 , 48 ]. Co-exposures, or studies where psychosocial stress may be the result of other life events such as starvation, were outside the scope of this review.…”
Section: Discussionmentioning
confidence: 99%
“…In this chapter, the authors find that the LCHD framework is of great value in both elucidating the sequelae of CKD risk and identifying the kinds of early life interventions that have the potential to mitigate it (Brophy et al 2017). …”
Section: Section Iii: the Life Course Origins And Consequences Of Spementioning
confidence: 99%
“…For example, while it is well established that exposure to aminoglycoside antibiotics early in life can have detrimental and potentially devastating effects on both auditory and renal function, the chapters in this volume by Russ and colleagues ) on hearing and Brophy and colleagues (Brophy et al 2017) on chronic kidney disease (CKD) suggest that there are ways that the developing sensory apparatus in the ear and the developing filtration apparatus in the kidney may share other potential vulnerabilities across the life course. Future research on how risks and protective factors influence multiple systems will potentially lead to multi-solving interventions that can optimize health development across several discreet physiological systems.…”
Section: Mechanism Researchmentioning
confidence: 99%
“…The suggestion that individuals with ASD have delayed maturation of key developmental processes also argues for a more developmentally attuned and integrated understanding of how to optimize outcomes. The chapter on CKD by Brophy and colleagues (Brophy et al 2017) also connects the dots between prematurity and other insults that may lead to decreased number of functional kidney filtration units (nephrons) and the time-specific and cumulative insults that are increasingly understood as the life course developmental pathway to CKD.…”
Section: The Health Development Of Particularly Vulnerable Populationsmentioning
confidence: 99%